Incentives versus sorting in tournaments: evidence from a field experiment - Edwin Leuven; Hessel Oosterbeek; Joep Sonnemans; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2008)
A vast body of empirical studies lends support to the incentive effects of rank-order tournaments. Evidence comes from experiments in laboratories and non-experimental studies exploiting sports or firm data. Selection of competitors across tournaments may bias these non-experimental studies, whereas short task duration or lack of distracters may limit the external validity of results obtained in lab experiments or from sports data. To address these concerns we conducted a field experiment where students selected themselves into tournaments with different prizes. Within each tournament the best performing student on the final exam of a standard introductory microeconomics course could win a substantial financial reward. A standard non-experimental analysis exploiting across tournament variation in reward size and competitiveness confirms earlier findings. We find however no evidence for effects of tournament participation on study effort and exam results when we exploit our experimental design, indicating that the non-experimental results are completely due to sorting. Treatment only affects attendance of the first workgroup meeting following the announcement of treatment status, suggesting a difference between short-run and long-run decision making.
Keywords: J33; 330; Tournaments; incentives; sorting; field experiments; Ranking-Verfahren; Test; Ökonomischer Anreiz; Entscheidungstheorie